If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1) = 3 Reorder the terms: (-1 + x) = 3 Remove parenthesis around (-1 + x) -1 + x = 3 Solving -1 + x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 3 + 1 Combine like terms: -1 + 1 = 0 0 + x = 3 + 1 x = 3 + 1 Combine like terms: 3 + 1 = 4 x = 4 Simplifying x = 4
| log(x-1)=3 | | 15/100=250/x | | 100-(7.84s/(100-0.075s)) | | y^4=8 | | 6(x+2)=10x-28 | | 4z+8=36 | | 16(4+4x)=5x-1 | | -2x/3=1 | | 12x-10=-24 | | -2x/31 | | 4m-7=85 | | 5+4a-(2a+2)-(5a+7)= | | 17x-21=119 | | -18x-4=-41 | | 18x-8=-23 | | 24x-2y=3 | | -4m-6=-3 | | 4t-6=-4 | | 8z+16=31 | | 11x+4=76 | | 19n-14=50 | | -2x^2+4x+16=x-4 | | 19p+10=138 | | 12p+9=90 | | 1=314.019418x+24673.20799626468y | | 9m-14=-2 | | ydx-(x^2-1)*dy=0 | | 9x-11=37 | | (6+2)x(12-9)= | | X-8y=-105 | | (8+2)x(12-9)= | | 8x-1=5x-10 |